SISTEM PENDUKUNG KEPUTUSAN KELAYAKAN PENERIMA KREDIT RUMAH DI PT. NGK JAMBI DENGAN MENGGUNAKAN METODE FMCDM - Yeni Nurjani; Tri Setia Ningsih (JURNAL AKADEMIKA)
The concept of Decision Support Systems (DSS) or Decision Support System (DSS) is a branch of artificial intelligence (artificial intelligence ) that is widely used. There are many methods that can be used by decision makers to help find the optimum solutions or alternatives to a problem. One such method is Fuzzy Multi - Criteria Decision Making (FMCDM). This method will help decision makers in situations where there are many alternative decisions with multiple criteria. The final project will apply the Decision Support Systems using Fuzzy Method of Multi Criteria Decision Making ( FMCDM ) determination of home loans to PT. NGK Jambi. Making the Decision Support System using Borland Delphi 7.0 programming language and supported by Microsoft Access 2007 as database processing, Data Input consists of alternative data, the data criteria, the data set of interest and set a match, the data processing is done by calculating the index is done by substitution interests of the rating and rating match, then the index in subtitusikan with the degree of optimism it will obtain the total value of the integral for each alternative. The recommendations based on the total value of the integral obtained the highest degree of optimism regardless. From the results of this study concluded that the presence of Decision Support System Determination of home loans to PT. NGK Jambi then it can help in the decision making process to the customer 's decision granting the cooperative and will facilitate in making the report of recommendations and reports customer.